Effect of Stopping Cotrimoxazole Preventive Therapy on Microbial Translocation and Inflammatory Markers Among Human Immunodeficiency Virus–Infected Ugandan Adults on Antiretroviral Therapy: The COSTOP Trial Immunology Substudy. (23rd October 2019) - Kyosiimire-Lugemwa, Jacqueline; Anywaine, Zacchaeus; Abaasa, Andrew; Levin, Jonathan; Gombe, Ben; Musinguzi, Kenneth; Kaleebu, Pontiano; Grosskurth, Heiner; Munderi, Paula; Pala, Pietro
Abstract: Background: Cotrimoxazole preventive therapy (CPT) in human immunodeficiency virus (HIV) infection is a World Health Organization–recommended standard of care in resource-limited settings, but the mechanism of CPT's beneficial effects is unclear. The COSTOP trial (ISRCTN44723643) evaluated the noninferiority of discontinuing CPT in stabilized patients on antiretroviral therapy. The COSTOP immunology substudy was conducted on a subset of COSTOP participants randomized to continue CPT (n = 86) or discontinue CPT (placebo, n = 86) as daily treatment for 1 year. Methods: We evaluated whether CPT reduces microbial translocation, indicated by the presence of bacterial lipopolysaccharide (LPS) and LPS control factors such as soluble CD14 (sCD14) and endotoxin core antibody (EndoCAb immunoglobulin M [IgM]) in plasma. Intestinal barrier damage as indicated by plasma intestinal fatty acid binding protein (IFABP), T-cell activation, and the inflammatory markers C-reactive protein (CRP), interleukin 6 (IL-6), and tumor necrosis factor α (TNF-α) were also evaluated. Results: We found no significant change in markers of microbial translocation (LPS, IFABP, sCD14, and T-cell activation), with decreased EndoCAb IgM. There was significant increase in inflammation markers (CRP and IL-6) after stopping CPT compared to those who continued CPT. Conclusions: These results add to the evidence of immunological benefits of CPT among HIV-infected populations in resource-limited settings. However, no evidence of reducing microbial translocation was observed. Abstract : Cotrimoxazole preventive therapy in antiretroviral therapy–treated adults with HIV infection reduces inflammatory markers but has no effect on markers of microbial translocation, intestinal barrier integrity, or T-cell and monocyte activation.